Factors associated with the quality of mental health services and consumers' functionality using tertiary‐based services. Issue 2 (3rd May 2021) - Badu, Eric; O'Brien, Anthony P.; Mitchell, Rebecca; Osei, Akwasi
Abstract: Purpose: Assess factors associated with the quality of mental health services. Design and Methods: Cross‐sectional design, quantitative data, and 510 consumers from three psychiatric facilities. Results: The average age of consumers was 34 years and 51.57% males. Consumers reported mixed satisfaction with the quality of mental health services (mean = 3.2; SD = 0.56) but were dissatisfied with the range of interventions (mean = 1.57; SD = 0.77). Predisposing (age, education, and primary occupation), enabling (insurance status), and need factors (mental health status) were significantly associated with quality indicators (range of interventions, efficacy, and overall satisfaction). These factors were significantly associated with consumers' functionality (cognition, mobility, self‐care, getting along, life activities, and participation). Practice Implications: Policymakers and clinicians are encouraged to incorporate the predisposing, enabling, and need factors into mental health planning, monitoring, and advocacy to improve service outcomes.